(untitled) (Research, Society and Development, 2021)
The aim of this study is to carry out a literature review about the interactions that can occur with the use of medicinal plants in the context of arterial hypertension. This is a narrative literature review, exploratory and qualitative in nature. In this study, articles searched in the main databases on the internet will be used: Virtual Health Library (VHL), Online Medical Literature Analysis and Retrieval System (MEDLINE), Scientific Electronic Library Online (SciELO). The medicinal plants presented to treat hypertension were Allium sativum, Alpinia zerumbet, Citrus sp., Passiflora sp., Cymbopogon citratus. The study revealed that among the main interactions involved in the use of medicinal plants associated with the use of drugs for the treatment of hypertension were of the pharmacodynamic type, which reveals the need to be cautious in associating the use of plants with drugs.